Cocaine added to heroin fails to affect heroin-induced brain hypoxia - Thomas, Shruthi A. (Brain Res, 2020)
Heroin and cocaine are both highly addictive drugs that cause unique physiological and behavioral effects. These drugs are often co-administered and cocaine has been found in ~20% of cases of opioid overdose death. Respiratory depression followed by brain hypoxia is the most dangerous effect of high-dose opioids that could result in coma and even death. Conversely, cocaine at optimal self-administering doses increases brain oxygen levels. Considering these differences, it is unclear what pattern of oxygen changes will occur when these drugs are co-administered. Here, we used high-speed amperometry with oxygen sensors to examine changes in oxygen concentrations in the nucleus accumbens (NAc) induced by intravenous (iv) cocaine, heroin, and their mixtures in freely-moving rats. Cocaine delivered at a range of doses, both below (0.25 mg/kg) and within the optimal range of self-administration (0.5 and 1.0 mg/kg) modestly increased NAc oxygen levels. In contrast, heroin increased oxygen levels at a low reinforcing dose (0.05 mg/kg), but induced a biphasic down-up change at higher reinforcing doses (0.1 and 0.2 mg/kg), and caused a strong monophasic oxygen decrease during overdose (0.6 mg/kg). When combined at moderate doses, cocaine (0.25, 0.5 mg/kg) slightly increased and prolonged oxygen increases induced by heroin alone (0.5 and 0.1 mg/kg), but oxygen decreases were identical when cocaine (1 mg/kg) was combined with heroin at large doses (0.2 and 0.6 mg/kg). Therefore, health dangers of speedball may result from de-compensation of vital functions due to diminished intra-brain oxygen inflow induced by high-dose heroin coupled with enhanced oxygen use induced by cocaine.